N. D. KONDRATIEV'S LONG WAVE THEORY AND MODERNITY: THE DIGITAL AGE - Dudin, Mihail; Levina, Elena; Alferov, Valery; Zasko, Vadim (Revista Inclusiones, 2020)
The object of this study is the "long wave" theory by N.D. Kondratiev. The purpose of this article is to study N.D. Kondratiev's long wave theory and its influence on the present. Methods. The authors of the article used such general scientific research methods as analysis and synthesis. Their choice was conditioned by the need to understand the influence of Kondratiev's long wave theory on modern economic reality. In particular, the authors used a systematic approach to analyze the system of economic indicators that cause wave-like changes in the economy, as well as empirical and economic-analytical methods to study open empirical data that explain the features of economic activity and the functioning of social actors.